They can and will: Preschoolers encourage pro-environmental behavior with rewards and punishments. (August 2022) - Hu, Chenhao; Wu, Zhen
Abstract: Although studies have shown that preschoolers can think pro-environmentally, whether they can act pro-environmentally, especially at a personal cost, remains unexplored. We directly investigated how 4–6-year-old preschoolers reacted to pro-environmental and anti-environmental behaviors within their sphere of influence. In two studies ( N  = 211), children were presented with vignettes that showed both pro-environmental and anti-environmental actions and completed three tasks: distributed stickers (reward) to the protagonists shown in the vignettes in Task I and distributed non-costly or costly unpleasant items (punishment) to the protagonists in Tasks II and III, respectively. Results showed that older children rewarded pro-environmental actions more than younger children did, while 4–6-year-olds consistently punished anti-environmental actions. Moreover, 6-year-olds (but not younger children) systematically reasoned and insisted on punishment, even at a personal sacrifice. Together, preschoolers can act pro-environmentally, suggesting that beginning early in their development, they show a behavioral capacity and willingness to encourage pro-environmental behavior. Highlights: Preschoolers can act pro-environmentally within their sphere of influence. Preschoolers reward pro-environmental behavior in an age-increased manner. Preschoolers consistently punish anti-environmental behavior when it is not costly. By age six, children can systematically reason and execute costly punishment.